Common Mental Disorders Among Adolescents Accessing HIV Treatment In Cape Town, South Africa - Mtukushe, Bulelwa (Department of Psychiatry and Mental Health, 2024)
Background: At the present time, data on the prevalence of common mental disorders (CMD) among adolescents living with HIV (ALHIV) in South Africa (SA) is limited. Studies that exist focus mainly on HIV-infected adults with mental health problems besides a few studies investigating depression and anxiety in children and adolescents living in SA. Research on the mental health of this vulnerable population remains very limited. Therefore, this study aims to address this gap by assessing the prevalence of CMD among adolescents living with HIV in SA; and determining the factors associated with CMD among this vulnerable population. Specific objectives: Specific objectives included, assessing the CMD among adolescents accessing ARV treatment; and determining factors associated with CMD among adolescents accessing HIV treatment. Methods: 121 Participants were recruited into the study through convenience sampling and interviewed. To be included in the study, participants had to be 10 to 19 years old; have knowledge of their own HIV-positive status; and presently on HIV treatment. Participants over 18 years were excluded if they did not provide informed consent and those under 18 were excluded if parent consent or adolescent assent was not obtained. Interviews with participants were conducted by study research assistants using a survey questionnaire which included the following mental health measures; Beck Depression Inventory for youth (BDI-Y), Beck Anxiety Inventory for youth (BAI-Y). Data collection for the study took place at two HIV treatment clinics in Cape Town, Groote Schuur hospital and Kuyasa clinic. Two logistic regression models were developed. Unadjusted and adjusted associations between socio-demographics, SES, food insecurity, alcohol use, years child known status and the presence of anxiety and depression were explored through logistic regression. Age, gender and variables that were significant in the unadjusted associations were included in the adjusted logistical regression models. Significance was set at p<0.05. Results: Four main findings emerged from the current study: 13.2% of participants were at risk for anxiety and 13.2% were at risk for depression; 6.6% participants were at risk for both anxiety and depression; the only variable associated with anxiety was socio-economic status and this was only significant in the unadjusted model; and the only variable associated with depression was highest level of schooling completed (i.e. currently in high school/completed high school) and this was significant in both unadjusted and adjusted models. Overall, adolescents with a higher educational level were less likely to develop depressive symptoms (adjusted model: OR=0.10, 95% CI 0.02-0.68). Conclusion: The present study assessed the prevalence of CMD, including determining the factors associated with CMD among adolescents accessing HIV treatment in Cape Town. Findings revealed that participants were at risk for anxiety, depression and comorbid anxiety and depression. Only highest level of schooling completed was found to be a protective factor against depression for this vulnerable population. Based on these findings, considerations for improving mental health outcomes for this population should include, screening for mental health conditions in ARV clinics, early identification and treatment of mental health problems, and evidence-based mental health counselling